An Examination of the Importance of Strain in the Cannabis Gateway Effect - McCutcheon, James C. (International journal of offender therapy and comparative criminology, 2018)
Gateway theory has been the source of much debate in both the research literature and public policy. Support for gateway sequencing has been mixed, especially in research that has considered the role of criminological variables in the etiology of substance use. For example, limited prior research has observed as important in gateway sequencing the effects of severe stressors. Data from the National Longitudinal Study of Adolescent to Adult Health are utilized to test gateway theory and examine whether severe stressors affect the relationship between frequency of cannabis use and later use of other illicit drugs (OIDs). Findings suggest that while frequency of cannabis use does increase the likelihood of later use of OIDs, this relationship may be the result of the common cause of experiencing severe stress. Implications of the findings are discussed.